2021
DOI: 10.1371/journal.pone.0245753
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of COVID-19 and preventive behaviors among waiters working in food and drinking establishments in Southwest Ethiopia

Abstract: Background Waiters working in different food and drinking establishments have a higher risk of contracting COVID-19 and transmitting the infection to others because they interact with many people. Most COVID-19 related studies in Ethiopia mainly focused on the general population, whereas, this study aimed to assess the knowledge of COVID-19 and preventive behaviors among waiters in Southwest Ethiopia. Methods A cross-sectional study was conducted from June 1 to June 15, 2020, among waiters working in food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
(20 reference statements)
7
17
2
Order By: Relevance
“…Overall, the comprehensive high self-efficacy in COVID-19 prevention was 50.4%, 95% CI (46.5–54.1). This finding is consistent with the study reporting that 53.1% of study participants had high self-efficacy towards COVID-19 prevention measures in Southwest Ethiopia [ 7 ]. Besides, a study across five continents demonstrated a significant drop in self-efficacy beliefs from before to during the lockdown [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, the comprehensive high self-efficacy in COVID-19 prevention was 50.4%, 95% CI (46.5–54.1). This finding is consistent with the study reporting that 53.1% of study participants had high self-efficacy towards COVID-19 prevention measures in Southwest Ethiopia [ 7 ]. Besides, a study across five continents demonstrated a significant drop in self-efficacy beliefs from before to during the lockdown [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Data were collected through a self-administered technique using a structured questionnaire. The data collection tool was prepared by referring to previous studies [ 7 , 9 11 ] and was amended to fit the study population and research objectives. The instrument consisted of five parts: baseline characteristics, chronic illness, and exposure to COVID-19 infection, students’ attitudes towards COVID-19 prevention measures, preparedness to combat the spread of COVID-19, and perceived self-efficacy to control and prevent COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An individual's perception of risk to themselves and their selfefficacy in addressing that risk influence the uptake of health preventive behaviors (Jørgensen et al, 2020). Fear is one part of an individual's analysis of risk, and subsequent health behaviors in the COVID-19 pandemic such as handwashing, mask-wearing, and physical distancing are enhanced by feelings of fear (Harper et al, 2020;Jørgensen et al, 2020;Qanche et al, 2021).…”
Section: Health Behaviorsmentioning
confidence: 99%